Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/adj.12711
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐short implants in the prosthetic rehabilitation of the posterior maxilla

Abstract: AimTo compare clinical outcomes of ‘extra‐short' and regular bone level implants in the posterior maxilla for 12 months after loading.Materials and MethodsTwenty‐three systemically healthy, non‐smoking patients received 30 extra‐short, 24 regular bone level implants. Acrylic stents were fabricated for each patient for correct implant positioning. Implant lengths were 4–6 mm in the test, 8/10 mm in the control group. Radiographic evaluation was performed at baseline, 6, and 12 months after loading. Crestal bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…As stated, short implants do not have a significant impact on marginal bone loss and the survival rate of implants. 7,32 Some studies also concluded that the survival rate of short implants is the same as that of regular implants placed through bone regeneration procedures, [33][34][35][36][37][38] which is in agreement with the results of this study that shows the acceptable outcomes of short implants throughout the three years follow-up, with an average amount of peri-implant bone resorption.…”
Section: Proper Implant Positioning Has Numerous Advantages Including...supporting
confidence: 90%
“…As stated, short implants do not have a significant impact on marginal bone loss and the survival rate of implants. 7,32 Some studies also concluded that the survival rate of short implants is the same as that of regular implants placed through bone regeneration procedures, [33][34][35][36][37][38] which is in agreement with the results of this study that shows the acceptable outcomes of short implants throughout the three years follow-up, with an average amount of peri-implant bone resorption.…”
Section: Proper Implant Positioning Has Numerous Advantages Including...supporting
confidence: 90%
“…For five of them 35‐37,41,44 the results were reported in multiple publications, so that a total of 25 articles 8,10,35‐57 were considered in the analysis. Thirty‐six articles 15,58‐92 were excluded after full‐text evaluation. Table 1 reports the list of excluded studies with the main reasons for exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…In one study, 4‐mm long implants were placed in non‐atrophic edentulous sites (11.5 mm below maxillary sinus/12.5 mm above the mandibular canal), and ST implants were placed in sites with similar RBH without any augmentation procedure 58 . In another study, implants of 4, 5, and 6 mm‐long were placed in sites of 4‐7 mm RBH, while ST implants were placed in sites with a mean RBH of 10.17 mm, without regeneration 61 . In spite of the interesting results provided, these protocols are not comparable to that addressed in our review, because the main clinical indications for SH implant (being an alternative to demanding and invasive augmentation procedures) seems not to be met by these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies were excluded based on the title and the abstract mainly due to the following reasons: type of study (retrospective, prospective study, case series), enrolment of fully edentulous patients, assessment of outcomes other than the primary outcome of our study, short implants defined as >6 mm, resonance frequency analyses, follow-up < 12 months after loading, studies including implants > 6 mm in the short implants group, and studies comparing clinical outcomes of short implants placed in anterior vs. posterior regions and not short vs. standard length implants. After the full texts were obtained, five studies were excluded for reasons associated with the study design; in particular two prospective studies [ 22 , 23 ], two retrospective studies [ 24 , 25 ], and one study allowing flapless implant placement in the test and not in the control group were excluded [ 26 ]. Additional reasons for excluding studies were the following: four studies included implants with length > 6 mm in the test group [ 24 , 27 , 28 , 29 ], one study reported a follow-up period < 1 year [ 30 ], two studies assessed outcomes other than the ones this review evaluates [ 31 , 32 ], in one non-randomized clinical trial the site of implant placement was unclear [ 33 ], and in one other study the implant surface characteristics were unknown [ 34 ].…”
Section: Resultsmentioning
confidence: 99%